2016
DOI: 10.2337/dc16-1682
|View full text |Cite
|
Sign up to set email alerts
|

Growth Differentiation Factor 15 as a Novel Biomarker for Metformin

Abstract: OBJECTIVEMetformin is a commonly used glucose-lowering drug. However, apart from glycemic measures, no biomarker for its presence or dose has been identified. RESEARCH DESIGN AND METHODSA total of 237 biomarkers were assayed in baseline serum from 8,401 participants (2,317 receiving metformin) in the Outcome Reduction with Initial Glargine Intervention (ORIGIN) trial. Regression models were used to identify biomarkers for metformin use. RESULTSGrowth differentiation factor 15 (GDF15) was strongly linked to met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
102
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(108 citation statements)
references
References 14 publications
5
102
0
1
Order By: Relevance
“…We also showed that metformin use was associated with elevated GDF-15 plasma levels and demonstrated that its contribution largely explains the consistent finding of increased plasma GDF-15 levels in T2D. 8 When all the relevant variables were entered into a multivariate model, a similar pattern was observed in both study groups and in the whole cohort, with NT-proBNP, age and serum creatinine emerging as the strongest predictors ( Table 1). The major difference was in the strength of the association with metformin in participants with T2D, which was much greater than and also independent of any other variable, being responsible for a 40% rise in GDF-15 level.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…We also showed that metformin use was associated with elevated GDF-15 plasma levels and demonstrated that its contribution largely explains the consistent finding of increased plasma GDF-15 levels in T2D. 8 When all the relevant variables were entered into a multivariate model, a similar pattern was observed in both study groups and in the whole cohort, with NT-proBNP, age and serum creatinine emerging as the strongest predictors ( Table 1). The major difference was in the strength of the association with metformin in participants with T2D, which was much greater than and also independent of any other variable, being responsible for a 40% rise in GDF-15 level.…”
Section: Discussionsupporting
confidence: 62%
“…Although still observed after adjusting for ongoing statin therapy, the achieved LDL cholesterol levels are likely to inversely reflect the overall cardiovascular risk of the patients. We also showed that metformin use was associated with elevated GDF‐15 plasma levels and demonstrated that its contribution largely explains the consistent finding of increased plasma GDF‐15 levels in T2D …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many mechanisms of action for the insulin sensitizing actions of metformin have been proposed 4 , few if any of these would explain the beneficial weight loss promoting effects of the drug which continue to be recognised 5 . A recent observational epidemiological study 6 noted a robust association of metformin use with circulating levels of GDF15, a peptide hormone produced by cells responding to a wide range of stressors 7 . GDF15 acts through a receptor complex solely expressed in the hindbrain, through which it suppress food intake [8][9][10][11] .…”
mentioning
confidence: 99%